Uji Pendahuluan Genotipe-genotipe Kedelai Hasil Seleksi In Vitro terhadap Cekaman Aluminium dan pH Rendah - Arief Vivi Noviati; Sri Hutami; Ika Mariska; Endang Sjamsudin (Jurnal AgroBiogen, 2005)
Aluminum toxicity is a major constraint to soybean production in acid soils. Since variabilities on Al tolerance in plants are very limited, mutation breeding, and in vitro selection were used to increase the variability. Three soyben genotypes were produced from cultivars Wilis and Sindoro that have been gamma irradiated and selected in vitro for their tolerance to Al on Al and low pH media. These genotypes and their original cultivars were then planted in a greenhouse in an acid soil on May 2001. The results showed that the plant performances were varied, some were shorter and more compact than the original. Based on the yield components, a number of plants from the genotypes showed higher than those of the control cultivars. These plants were considered more tolerant to Al than the original cultivars.